Estrutura interna de depósitos eólicos do estado do Ceará: radarfácies e evolução - Lima Júnior, Sérgio Bezerra (2017)
The understanding of coastal dynamics is the starting point for understanding the evolution of these environments by determining their morphology and sedimentary sequence. In the geological record, these features are identified mainly by the preservation of the internal sedimentary structures formed in the various points of the deposits influenced by two main factors: the wind intensity and variation of the direction and the gravity that acts facilitating the sliding in the line of greater slope. It is necessary to investigate the internal architecture of the features, as well as thickness of the layers, determination of the water table and the recognition of erosive and depositional records to relate to the different types of dunes or sedimentary deposits. Among the various methods of investigation (i.e. trenchs, wells and others), the most relevant are the geophysical methods. One of the most important is the ground-penetrating radar (GPR), which uses high frequency electromagnetic waves for this investigation. Three areas of study were chosen in the present research to compare and investigate the evolution of these complex coastal wind environments in the state of Ceará, both on the East coast and on the West coast, namely: The isolated barchan dunes of Jericoacoara Beach, depositional lobe of the blowouts of Porto das Dunas and the sandsheets of Praia do Futuro, characterizing the different forms of deposits existing in the Northeastern coast. The main objective of this research is to deepen the study on the imaging of internal structures of aeolian dunes and to propose a model for the evolution of these deposits of the coast of Ceará, fact this unprecedented for the State. As a conclusion, in relation to the Jericoacoara area, it can be observed that the isolated barchan dunes present, in the main direction of the strong wind, angles of response of the foresets from the windward zone, approximately 34º, which are clearly slope angles of Slip Face, that is, the angles of response remain almost constant in this profile. Indicating that the barchan dune migrates preserving the slip face. In order to investigate this variation, it was necessary to carry out another acquisition campaign with a higher level of detail using the antenna with a higher frequency, in order to improve the vertical resolution, due to the distance between the foresets, on a centimeter-order, and also to collect a greater number of profiles. It suggests that actual angles of response are observed in the 3D GPR cube as a surface interconnecting the apparent angles and being pointed towards a direction of an imaginary point (P) located at the center point of a circle traced along the base of the sliding face (Slip Face). In relation to the migration of the dune, it is possible to observe that there are variations of migration speed over the considered time and that, in general, a migration rate of 16 meters per year, with a total displacement to the West of 900 meters in the Period of 57 years, corroborating this average with several data from the literature. In reference to the internal structure of the depositional lobes, it is observed a sequence of excavations (concave forms) and filling with angles close to 34º, deposition by sliding, and smaller angles of 2º-3º, laminar type deposition. The sandsheet of Praia do Futuro was constructed through several parallel depositional lobes that built this extensive deposit so peculiar of the coast.